The representation of Chinese people in the magazine Costa Rica de Ayer y Hoy (1949-1971) - Chen Mok, Susan (2024)
The objective of this research is to compile and analyze the texts of the magazine Costa Rica de Ayer y Hoy, from 1949 to 1971, related to people of Chinese descent. This was done in order to learn the type of information that was published about this community, as well as their perceived contributions, according to the representations given by the press releases. This magazine was selected because it is of Puntarenas origin, of a cultural and historical nature, and without political interference, as established by its editor and owner. The work uses qualitative research methods of content and descriptive analysis to establish the journalistic notes obtained from the primary sources, which were the published editions found in the National Library System of Costa Rica. The results show that most of the press releases are of commercial content, but also an important part of historical content. In less quantity, there are those of educational, sports, social, community and literary content. The analysis concludes that, according to this magazine, the Costa Rican Chinese community has contributed to the development of the communities where they are established.